MANAJEMEN PENGGUNAAN MEDIA DIGITAL DI PAUD TERHADAP PERKEMBANGAN BAHASA ANAK USIA DINI - Faviandhani, Qausya; Rofiyarti, Fitri (MOTORIC, 2025)
ABSTRACT This study aims to analyze the management of digital media use in early childhood education (PAUD) and its impact on the language development of young children. The research approach used a mixed method with a sequential explanatory design. Quantitative data were obtained through questionnaires and observations of children's language development, while qualitative data were obtained through interviews and in-depth observations. The study sample consisted of 40 PAUD teachers and 80 children aged 4–6 years from three PAUD institutions in Surabaya and Sidoarjo. The results showed that digital media management which includes planning, media selection, duration settings, mentoring, and evaluation has a significant impact on children's language development (p < 0.05). PAUDs that implement structured digital media management show better achievements in vocabulary development, speaking skills, and listening skills than PAUDs that do not have clear media management. Qualitative analysis shows that teacher mentoring is a key factor in ensuring that digital media use is interactive, not passive. These findings emphasize the importance of effective digital media management in supporting the stimulation of early childhood language development. Keywords: Digital Media Management, Early Childhood Education, Language Development, Early Childhood